Fighting to Swear the Warsaw Confederation from May 17th 1573 to April 22th 1574 in the Light of “Diariusz poselstwa polskiego do Francji” to Henry III in 1573 - Wasiak, Kornelia (Vade Nobiscum, tom XXII/2021: Studia z wieków dawnych, 2021)
The article is a reconstruction of one of the stages of the struggle to include in the formal and legal framework the provisions on religious tolerance contained in the act of the general Warsaw confederation, written in 1573. It covers the time from the election of Henri de Valois (11 May 1573) to the end of the king’s coronation parliament (24 April 1574). The article consists of three parts. The introductory fragment outlines its purpose and also contains information about sources and literature. The elaboration describes particular events related to the fight for religious tolerance along with the accompanying atmosphere as well as the motives and way of work of individual participants in these events. The end of the text contains conclusions based on the description.